Depression, Neuroticism, and Urinary Incontinence in Premenopausal Women: A Nationwide Twin Study. (28th August 2013) - Tettamanti, Giorgio; Altman, Daniel; Iliadou, Anastasia N.; Bellocco, Rino; Pedersen, Nancy L.
Abstract : Previous studies have found that major depression and neuroticism are positively associated with urinary incontinence (UI). However, the genetic contribution to these associations has never been investigated. In 2005, a total of 14, 094 female twins born 1959–1985 in the Swedish Twin Registry participated in a comprehensive survey on common exposures and complex diseases. Structured questions provided information on UI, depressive symptoms, major depression, and neuroticism. A logistic regression model based on generalized estimating equations (GEE) was used to estimate odds ratios (ORs) with 95% confidence intervals (CIs). Environmental and genetic influences were assessed in co-twin control analyses and quantitative genetic analyses, which were also used to determine the proportion of the phenotypic correlation explained by familial factors. Major depression, depressive symptoms, and neuroticism were positively associated with all UI subtypes (overall, stress, urge, and mixed UI). In a trivariate Cholesky model with neuroticism, depressive symptoms (or depression), and UI a modest genetic correlation was found between indicators of depression and overall, or stress, UI. The majority of this correlation was independent from neuroticism. In contrast, the genetic factors shared between indicators of depression and urge or mixed UI were entirely in common with neuroticism. In conclusion, depression and neuroticism are associated with UI among premenopausal women: the associations are in part determined by genetic factors in common to the disorders.